Using tools for sequence alignment and outline of phylogenetic trees to determine species - Madrigal-Valverde, Karla Alejandra (2017)
This article focuses on the bioinformatics software tools and bioinformatics algorithms that are used to provide more accurate results in determining species. This project was conducted in collaboration with the Research Center of the “Universidad Iberoamericana de Ciencia y Tecnología, Santiago de Chile”. It was determined, by use of software programs which run algorithms to create phylogenetic trees, that a sample of an unknown specie not necessarily belongs to a known specie, although they can be morphologically identical.